2013
DOI: 10.1002/app.39715
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of PVA doped with algal glycerol

Abstract: Physical behavior of membrane blends of poly(vinyl alcohol) (PVA) doped with different weight percentage (wt %) of algal glycerol is reported. Solid-state PVA/glycerol membranes were prepared by the solution casting method. Electrical impedance measurements were conducted to test the effect of varying the percentage of glycerol on the conductivity of the membranes. The measurements were made in the frequency and temperature ranges 1 Hz-1 MHz and 303-423 K, respectively. It was observed that the ionic conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…This process arises at high frequencies where the movement of ions is minimal due to their high relaxation time. It should be noted here that the second semicircle in Figure (a) can be related to the mass migration process where ionic species exhibit large relaxation time thus they diffuse to the electrodes where they accumulate …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process arises at high frequencies where the movement of ions is minimal due to their high relaxation time. It should be noted here that the second semicircle in Figure (a) can be related to the mass migration process where ionic species exhibit large relaxation time thus they diffuse to the electrodes where they accumulate …”
Section: Resultsmentioning
confidence: 99%
“…In previous investigations, the influences of blending PVA with different ratios of plasticizers on electrical, structural, and mechanical properties of the membranes were examined. The studies demonstrated that the addition of plasticizers to PVA enabled the control of its electrical conductivity and decreased the interaction among the macromolecules that increased the flexibility of its membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies investigated the effect of adding ionic liquids on the electrical properties of insulating polymers. The results revealed that insulating polymers act as semiconducting materials when mixed with ionic liquid at specific ratios [50,51]. An example of an environmentally-friendly ionic liquid is glycerol, which is believed to serve both as electrolytes and diffusion barriers [52].…”
Section: Introductionmentioning
confidence: 99%
“…Poly(vinyl alcohol) (PVA) is widely used in PV applications for the separation of water mixtures due to its water absorption properties 38,39 and its simplicity for membrane preparation. 23,[40][41][42] In particular, a recent study used commercial hydrophilic PVA-based membranes for the dehydration of highly alkaline ternary mixtures composed of glycerol, water, and potassium carbonate with PV.…”
Section: Introductionmentioning
confidence: 99%